Prospects for Russia–India Relations in the Indian Ocean Region. (2nd January 2017) - Srivastava, Nitika
ABSTRACT: The Indian Ocean can be a convergent and cooperative maritime space for India–Russia relations. Russia can achieve its ambitions to re-emerge as a "great power" and as an influential global player in international politics, while India can reinforce its dominance in the region. Since the 18th century, Russia has sought a presence in the Indian Ocean, and there is a long history of Soviet naval forces operating in the region. However with the disintegration of the Union of Soviet Socialist Republics (USSR), its influence was reduced dramatically. The increasing importance of the Indian Ocean to Russia has been driven by the fact that it is the home to two competitive economies – China and India – along with other emerging Indian Ocean Region countries. On the other hand, increasing Chinese activity, especially its ambitious One Belt One Road (OBOR) initiative through the Indian Ocean Region, and Russia's interest in joining the China–Pakistan Economic Corridor (CPEC) may have threatened India's interests. While considering Russia–India relations, little has been explored beyond defence cooperation. Besides, India's cold response to the OBOR initiative may lead to its marginalisation in the region. In this context, an effective India–Russia political, economic and military collaboration in the Indian Ocean would be beneficial for both India's security and Russia's aspirations in the Indian Ocean.